Description of all stages of a new tick species from California, Haemaphysalis vespertina (Acari: Ixodidae), with redescription of H. leporispalustris Packard, 1869 adults and phylogenetic relationships among related U.S. taxa - Egizi, Andrea; Nava, Santiago; Nakano, Angie; Saunders, Megan E. M.; Maestas, Lauren P.; Angelus, Autumn D.; Noden, Bruce; Nadolny, Robyn M.; Bajwa, Waheed I.; Lubelcyzk, Charles; Bhosale, Chanakya R.; Paskewitz, Susan; et al. (Zootaxa, 2025)
All active stages of Haemaphysalis vespertina sp. nov. (Acari: Ixodidae), a tick previously identified as H. leporispalustris Packard, 1869, are described from specimens collected on the vegetation and from leporids in California and Oregon. The adults of H. leporispalustris Packard, 1969 are redescribed based on type material. Adults of the two species can be distinguished by their overall size, the dorsal shape of palpal segment II, the number and shape of dorsal and ventral setae on palpal segment II, the number of spurs on coxae II, the length of setae on scutum, legs and coxae, and the pattern of scutal punctations. Phylogenetic analyses support H. vespertina as a distinct taxonomic lineage. Additional unresolved lineages within H. leporispalustris s.l. were identified, suggesting a need for further taxonomic study of leporid-associated Haemaphysalis ticks in North America.